Effects of client probability of failure, auditor characteristics, ownership structure on issuance of going concern opinion - Osman, Mohammad Noor Hisham (2016)
International Standard in Auditing 570 (ISA 570) mentions that auditors are responsible (1) to gather evidence about the reasonableness of management in applying going-concern assumption during financial statement preparation, and (2) to conclude about a client company's ability to continue operating in the foreseeable future (para. 6). The instance an auditor issues a going concern opinion (GC opinion) in the appropriate situation can be seen as an indicator of high audit quality, however, such a good case is an ideal rather than a reality. Inappropriate GC opinion issuance, in which (i) an auditor issues GC opinion to viable client [Type I Errors] or (ii) does not issue GC opinion to a client which later fails [Type II Errors], is common at international and local levels. Issuing GC opinion accurately is important because it implies the auditor is protecting the stakeholder’s interest. In the case of Enron, if Arthur Andersen (the company’s audit firm since it was set up) had issued GC opinion one year prior to the company’s collapse, billions of stakeholders’ money could have been saved. Even though the importance of GC opinion is a fact, there are still unresolved matters in the literature related to the determinants of GC opinion issuance. This brings to light the need for additional research on GC opinion and variables associated with it. Accordingly, this thesis is an attempt to examine the effect of selected factors on the propensity of GC opinion issuance in Malaysia. To be specific, this study investigates the interplay between the probability of client failure, auditor characteristics, ownership structure and GC opinion issuance. This study uses agency theory as a framework to develop 13 hypotheses and tested them on data accumulated from annual reports of financially distressed Malaysian public listed companies. Panel data from 2006 to 2012 on a sample of 644 observations have been analyzed using logistic regression. It is found that certainty (rather than probability) of client failure affects the issuance of GC opinion. Auditor characteristics of specialization, tenure and fee do not directly predict the issuance of GC opinion. The level of management and family ownership does moderately affect the relationship between certain auditor characteristics and GC opinion issuance. This study is a contribution to auditing literature as its findings can enhance our understanding about audit quality; particularly on the variables that are associated with the issuance of GC opinion. The output of this study which clarifies the GC opinion issuance process is useful for stakeholders, auditors and policy makers.